An Empirical Investigation of CDS Spreads Using a Regime Switching Default Risk Model - Milidonis, Andreas (2016)
Default risk in equity returns can be measured by structural models of default. In this paper we propose a credit warning signal (CWS) based on the Merton default risk (MDR) model and a Regime-switching default risk (RSDR) model. The RSDR model is a generalization of the MDR model, comprises regime-switching asset distribution dynamics and thus produces more realistic default probability estimates in cases of deteriorating credit quality. Alternatively, it reduces to the MDR model. Using the dataset of US credit default swap (CDS) contracts we construct rating based indices to investigate the MDR and RSDR implied probabilities of default in relation to the market-observed CDS spreads. The proposed CWS measure indicates an increase in default probabilities several months ahead of notable increases in CDS spreads.